The Influence of Economic Pressures and Gender Roles to Family Resilience During Covid-19 Pandemic : The Influence of Economic Pressures and Gender Roles to Family Resilience During Covid-19 Pandemic - Indah Sukmawati; Herien Puspitawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2021)
The existence of Covid-19 has changed the socio-economic life of the community. This study aims to analyze the effect of family characteristics, economic pressure, and gender roles on family resilience during the Covid-19 pandemic. Respondents in this study were wives from intact families with children scattered in Bogor Regency. The design of this research is a cross-sectional study with a sampling technique using purposive sampling method with a total sample of 84 families conducted in March 2021. The data processing uses descriptive tests, correlation test, and multiple linear regression tests. The results of the study found that most of the family's economic pressure and gender roles were in the low category. However, most of the family resilience is in the high category. The results of multiple linear regression analysis show that there is a significant negative effect of economic pressure on family resilience. There is a significant positive effect of gender roles on husband's income.